Nurse perception of care of hospitalized older adults - a comparative study between northern and central regions of Portugal - João Paulo de Almeida Tavares; Alcione Leite da Silva; Pedro Sá-Couto; Marie Boltz; Elizabeth Capezuti (Universidade de São Paulo, 2017)
Resume Objective: to analyze the relationship between the perceptions of nurses about geriatric care (GC) environment and geriatric nurses' knowledge and attitudes according to unit type considering the northern and central regions of Portugal. Method: a cross-sectional study was developed among 1068 Portuguese's nurses in five hospitals. The instrument was Geriatric Institutional Assessment Profile - Portuguese version. The independent samples t-test was when the assumption of normality was verified, otherwise, the Mann-Whitney U test was used. The level of significance was 5%. Results: the profile of perceptions of GC showed a relatively homogeneous pattern (no statistically significant results were found). For the geriatric care environment scale, only the CC/ED units presented significant differences in all considered subscales (resource availability; aging-sensitive care; institutional values; and continuity of care), with more positive perceptions among nurses in the northern region. In Professional Issues scales, only the scale perception of burden related with upsetting behaviors revealed significant differences between regions in all specialties. Conclusion: the findings suggest the need for increased investment by hospital leaders to promote a geriatric nursing practice environment that supports the specialized needs of hospitalized older adults.